PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VA SD NEGERI 023 SEDINGINAN KECAMATAN TANAH PUTIH - Jummiati '; Hendri Marhadi; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Absract: The problem this research is the students achievement of sains studies SD Negeri 023 Sedinginan Kecamatan Tanah Putih fourth graderes still low with an average value of 62,14 and minimum completeness criteria (KKM) sains studies is 70. Between students, amounting to 21 people only 7 students who achieve classical KKM with 33,33 %. This research is Classroom Action Research (CAR), which aims to improve the student achievement of sains studies class VA at SD Negeri 023 Sedinginan Kecamatan Tanah Putih with implementation approach CTL. Formulation of the problem : Is the implementation of approach CTL can improve students achievement of sains studies at SD Negeri 023 Sedinginan Kecamatan Tanah Putih. The research was conducted on April 11, 2016 to Mei 09, 2016 by 2 cycles. Subjects were students of SD Negeri 023 Sedinginan Kecamatan Tanah Putih, totaling 21 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 62,14. in the first cycle improve an average 72,28  and an improve in the second with an average of 88,10. Activities of the teacher in the learning process in cycle of 58,33% and the second meeting improve 72,22%. Cycle II first meeting and the second meeting improve 80,55% and the second meeting improve 86,11%. Results of data analysis of students activities in the first cycle with the first meeting of an average 55,55% and a second meeting improve to 72,22% . Cycle II first meeting improve 77,73% and the second meeting improve to 83,33%. Resultsin the class VA at SD Negeri 023 Sedinginan Kecamatan Tanah Putih that the implementation of approach CTL can improve student achievement of sains studies at fourth graderes SD Negeri 023 Sedinginan Kecamatan Tanah Putih. Key Words : Approach, Contextual Teaching and Learning (CTL), Students Achievement, Sains.